1992
DOI: 10.1557/jmr.1992.0961
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistance of metallic contacts on silicon and germanium during indentation

Abstract: The effects of indentation on the electrical resistance of rectifying gold-chromium contacts on silicon and germanium have been studied using nanoindentation techniques. The DC resistance of circuits consisting of positively and negatively biased contacts with silicon and germanium in the intervening gap was measured while indenting either directly in the gap or on the contacts. Previous experiments showed that a large decrease in resistance occurs when an indentation bridges a gap, which was used to support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Using a large Vickers indenter, the resistance of Si between two metal contacts was observed to decrease sharply at the point of phase transformation and return to its original value on unloading. Subsequent work by Clarke et al (1988), Pharr et al (1992) and Mann et al (2000) used the fact that metallic (β-Sn)-Si caused a Schottky to Ohmic contact on low-doped Si to monitor the onset of the phase transformation. Furthermore, Bradby et al (2003) fabricated a test structure on epitaxial Si wafers to quantitatively measure the current flow (again using a Schottky to Ohmic conversion at phase transformation to turn on current).…”
Section: Electrical Measurements 41 In Situ Electrical Measurementsmentioning
confidence: 99%
“…Using a large Vickers indenter, the resistance of Si between two metal contacts was observed to decrease sharply at the point of phase transformation and return to its original value on unloading. Subsequent work by Clarke et al (1988), Pharr et al (1992) and Mann et al (2000) used the fact that metallic (β-Sn)-Si caused a Schottky to Ohmic contact on low-doped Si to monitor the onset of the phase transformation. Furthermore, Bradby et al (2003) fabricated a test structure on epitaxial Si wafers to quantitatively measure the current flow (again using a Schottky to Ohmic conversion at phase transformation to turn on current).…”
Section: Electrical Measurements 41 In Situ Electrical Measurementsmentioning
confidence: 99%
“…The experimental methods for characterization of phase transformation include electrical resistance test [1], Raman spectroscopy [2-6], cross-sectional transmission electron microscopy [3-5], and scanning electron microscopy [2,4,5]. Previous studies indicated that nanoindentation-induced phase transformation of monocrystalline silicon occurred, and Si-III, Si-XII, or amorphous-Si were detected after unloading [1-6]. Molecular dynamics simulation could directly observe the phase transformations of silicon and their distribution, as well as the anisotropic behavior of single crystal, during nanoindentation in detail at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant works include (but are not limited to):Armstrong et al (1996);Bradby et al (2000Bradby et al ( , 2001Bradby et al ( , 2003;Clarke et al (1988);Chang and Zhang (2009c, 2008, 2009a); Chaudhri et al (2007); Cook (2006); Domnich et al (2000); Domnich and Gogotsi (2002); Domnich et al (2008); Fujisawa et al (2008); Jang et al (2005); Jian et al (2010); Juliano et al (2003, 2004); Khayyat et al (2007); Kailer et al (1997); Gerbig et al (2011); Puech et al (2004); Zarudi et al (2004);Chang and Zhang (2009b);Zhang and Basak (2013);Callahan and Morris (1992);Mann et al (2000Mann et al ( , 2002;Rao et al (2007);Ruffell et al (2006Ruffell et al ( , 2007b;Svechnikov et al (2007);Vandeperre et al (2007);Weppelmann et al (1993Weppelmann et al ( , 1995;Wu et al (1999);Zarudi and Zhang (1999);Zarudi et al (2003Zarudi et al ( , 2005;Zhang and Mahdi (1996);Zhang and Tanaka (1999);Pharr et al (1989Pharr et al ( , 1990Pharr et al ( , 1991Pharr et al ( , 1992;Haberl et al (2012).…”
mentioning
confidence: 99%